2012
DOI: 10.4161/nucl.21222
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes without a 30-nm chromatin fiber

Abstract: How is a long strand of genomic DNA packaged into a mitotic chromosome or nucleus? The nucleosome fiber (beads-on-a-string), in which DNA is wrapped around core histones, has long been assumed to be folded into a 30-nm chromatin fiber, and a further helically folded larger fiber. However, when frozen hydrated human mitotic cells were observed using cryoelectron microscopy, no higher-order structures that included 30-nm chromatin fibers were found. To investigate the bulk structure of mitotic chromosomes furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 64 publications
9
111
0
1
Order By: Relevance
“…Experimentally, many features of mutual interactions of chromatin fibers remain obscure, partly because of different chromatin forms that can potentially coexist in vivo [27]. Here, one should distinguish between the subtleties in interactions due to the complexity of the internal chromatin structure and due to different biophysical mechanisms likely to be involved.…”
Section: Interactions Between the Chromatin Fibersmentioning
confidence: 99%
“…Experimentally, many features of mutual interactions of chromatin fibers remain obscure, partly because of different chromatin forms that can potentially coexist in vivo [27]. Here, one should distinguish between the subtleties in interactions due to the complexity of the internal chromatin structure and due to different biophysical mechanisms likely to be involved.…”
Section: Interactions Between the Chromatin Fibersmentioning
confidence: 99%
“…Due to this complexity and the lack of existing optical techniques that can rapidly sample information below 200 nm, little is known about the higher-order chromatin structure at length scales between 10 and 200 nm or their dynamics in live cells (e.g., the folding structure of chromatin above that of mononucleosomes). Results from fixed-cell-imaging techniques, such as electron microscopy or SRM, have shown that chromatin between 20 and 200 nm is first organized into polynucleosomal 10-nm fibers, and in certain conditions, these fibers have been shown to assemble into 30-nm clusters (8)(9)(10), although the existence of the 30-nm fiber is a subject of an active debate. At length scales between 100 and 200 nm, recent work using SRM has shown a power-law (fractal) relation in the organization of chromatin, with domains of highly dense, inactive chromatin localizing within a few hundred nanometers of transcriptionally active sites (11).…”
Section: Significancementioning
confidence: 99%
“…Simple models such as the semi-flexible chain model based on the persistence length of the polymer may not be generally reliable. The reported persistence length spans a broad range from 30 nm to 300 nm, 41,42 reflecting the sensitivity of the system to the environmental variables previously discussed.…”
Section: B Chromatin Linearizationmentioning
confidence: 99%
“…35,38 Furthermore, more recent evidence suggests that even the regular 30-nm fiber structure does not exist consistently in living mammalian cells. 37,41,42 Hence, our current understanding of chromatin structure suggests that the chromatin in a cell exists in a melt-like dynamic state, providing greater accessibility for biological purposes than the conventional static model. 41 Also on a primary structural level, there are small variations in aminoacid sequences even though core histones are highly conserved proteins across species.…”
Section: Challenges In Chromatin Analysismentioning
confidence: 99%